Fabrication of Composite-Based Biosensors for Rapid Disease Detection - Nikandish, Mehrasa; Alsayegh , Hawraa; Karbalaee , Mojtaba; Yadollahi Nooshabadi, Narjes Sadat; Abazari, Mohammad Borhan (Journal of Composites and Compounds, 2024)
Biosensors are a fundamental component of point-of-care diagnostic technologies, which are essential for early detection and real-time health monitoring. They play a vital role in improving healthcare outcomes and making a significant societal impact by facilitating rapid diagnostics and disease management. This review explores the fundamentals of biosensors, including their operational principles, key components, and mechanisms, as well as the use of composite materials and their applications in disease detection. Furthermore, it discusses important performance metrics such as sensitivity, specificity, response time, stability, and reproducibility, while also addressing challenges related to cost and scalability.